The teaching of sex reversal and the effect of hormones in the expression of sex in biology classes - Gatchalian, Gloria Castro (1969)
The major purpose of this study was to show the effect of hormones in the development of sex and the process of sex reversal by observation, experimentation and verification. It was confirmed that the Bidder's organ is a rudimentary ovary, and that the presence of the test is an inhibitory factor to the further development of the Bidder's organ into an ovary. It was discovered that toads, neither too old nor too young, have the competency to respond to hormonal administration that enhanced better sex differentiation. Also, young cells (but not too young) have the greater potency to differentiate into other parts. Old toads are less susceptible to hormone stimulation.
Thesis (M.A. Biology Education)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching (Secondary) -- Philippines; Hormones, Sex; Sex differentiation